1D@2D Hierarchical Structures of Co(OH)x Nanosheets on NiMoOx Nanorods Can Mediate Alkaline Hydrogen Evolution with Industry‐Level Current Density and Stability. Issue 10 (1st September 2022) - Sun, Kai Zhi; Wen, Chun Fang; Qu, Xue; Liu, Peng Fei; Yang, Hua Gui
Abstract: Developing efficient electrocatalysts at ampere‐scale current densities is of paramount importance to advance industrial applications of alkaline water electrolysis. Herein, a hierarchical nanostructured electrocatalyst with two‐dimensional Co(OH)x nanosheets grown on one‐dimensional NiMoOx nanorods over three‐dimensional porous Ni foam substrate is designed. The resulting catalyst delivers ultrahigh hydrogen evolution reaction (HER) activity in the alkaline solution, which only requires overpotentials of 185 and 332 mV to achieve the current densities of −500 and −1000 mA cm –2 in 1.0 m KOH, respectively, and shows robust stability at −1000 mA cm –2 for 11 days. The unique 1D @ 2D hierarchical structures with abundant hetero‐interfaces can not only expose sufficient active sites but also boost alkaline HER kinetics with fast water dissociation ability. This present work may pave a new insight to design efficient electrocatalysts with hierarchical structures for alkaline HER with industry‐level current density and stability. Abstract : 1D @ 2D hierarchical nanostructured Co(OH)x  @ NiMoOx  @ nickel foam electrocatalyst is constructed through a controllable multi‐step process, with in situ formed Co hydroxides facilitating water dissociation, which exhibits outstanding hydrogen evolution reaction activity in 1.0 m KOH with overpotentials of 185 and 332 mV to achieve current densities of −500 and −1000 mA cm −2, respectively.